(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
This study analyzes the geochemical differentiation of chemical elements in irrigated clogged soils and compares their distribution with lithospheric Clarke values. The research evaluates the changes in physical-chemical and geochemical parameters driven by clogging and examines the migration and accumulation potential of major elements. A comparison of logarithmic Clarke values revealed Fe, Mn, Sr, and Ba as key indicators of clogging intensity. In weakly clogged soils, reduced concentrations of Cr, Ni, Co, W, and U reflect limited mobility. These findings contribute to understanding the geochemical genesis of clogged soils and serve as a basis for geochemical zoning.